Inequality and Income Distribution in Georgia - Ruslan Yemtsov (Institute for the Study of Labor (IZA), 2001)
In the period of macroeconomic crisis in Georgia between 1991 and1994 the combination of hyperinflation, catastrophic output drop and weak governance, have led to a sharp rise in inequality among households. Sharp inequities have arisen not only between households, but also between regions. This paper gives a picture of the main channels of redistribution and of the main driving forces of income inequality in Georgia, as it emerges from the analysis of the first representative survey of incomes and expenditures of Georgian households in 1996-1997. The paper finds that the level of inequality for money income in Georgia is comparable to highest inequality countries of Latin America (Gini equals 0.6). However, given the degree of informalization and demonetization of the economy, measuring only reported monetary incomes gives a somewhat misleading picture of the living standards. The paper argues that consumption is a much better indicator of welfare, especially in the Georgian context and explores the relationship between income and consumption in the Georgian context. Using consumption, we get the picture that is marked by very clear, though, not as striking inequalities (Gini coefficient of 0.36). Growth has not yet had a strong impact on consumption inequality per se, but we find evidence that during 1996-97 consumption increased at almost all levels of the distribution. During the same period, there was significant income mobility, except for those at the very bottom or the very top of the income distribution. For the latter, economic success appears to be closely associated with labor market status, ownership of productive assets and resulting earnings opportunities. Georgian economy is generating a system of much inequality. The key share of inequality can be attributed to informal incomes (using the decomposition analysis as proposed by Shorrocks). State transfers being reduced to minimum levels do exercise only a slight positive impact on the overall inequality outcomes.
Keywords: I3; J4; 330; Returns to education; in-kind income; poverty; income mobility; unreported incomes; Theil entropy index; mean log deviation index; Einkommensverteilung; Verbraucherausgaben; Disparitätsmaß; Übergangswirtschaft; Georgien